Analisis kandungan gizi tepung lokal (ubi ungu) termodifikasi sebagai bahan dasar pembuatan snack balita untuk pencegahan stunting - Anita, Anita; Ifadah, Raida Amelia; Yaqin, Ainul (Universitas Musamus, Merauke, Papua, 2023)
The aims of this research is to increase the nutritional value of purple sweet potato flour by fermentation method using Rhizopus oryzae mold. The research method used a factorial Randomized Group Design with factors of fermentation time (48 hours, 72 hours and 96 hours) and the amount of Rhizopus oryzae mold (20gram, 30gram and 40gram). The number of treatments was 9 treatments, namely T1N1 (48 hours: 20 grams of yeast), T1N2 (48 hours: 30 grams of yeast), T1N3 (48 hours: 40 grams of yeast), T2N1 (72 hours: 20 grams yeast), T2N2 (72 hours: 30 grams yeast), T2N3 (72 hours with 40 grams yeast), T3N1 (96 hours: 20 grams yeast), T3N2 (96 hours: 30 grams yeast) and T3N3 (96 hours: 40 grams yeast). Parameters observed were carbohydrate, protein, fat and fiber content. Data were tested with ANOVA and BNJ further test at the 5% level. The results showed that fermentation time and the amount of yeast given had an influence in each treatment. The best carbohydrate content was found in the T1N2 treatment 86.73%, the best protein content was found in the T3N3 treatment 18.835%, the best fat content was found in the T1N1 treatment 0.25% and the best fiber content was found in the T1N1 treatment 24.71%. Fermentation time and the amount of yeast had a significant effect on protein and fiber content but no significant effect on carbohydrate and fat content. The best treatment of 9 treatments for carbohydrate, protein, fat and fiber content was found in the T1N1 treatment with a treatment value of 0.727. The best fermentation treatment on fermented purple sweet potato flour can be used as an ingredient for making toddler snacks as a prevention of stunting and adjusted to the MP-ASI biscuit standard SNI 01-7111.2-2005.